SOCIAL BEHAVIOR COMMUNITY PUBLIC UNITED NOTHING KINGDOM (Study Phenomenology Punk Community In Blitar City) - Erawanto, Udin; Siswanto, Budi; Hariyanto, Tommy (IJRDO - Journal of Social Science and Humanities Research, 2017)
The purpose of the study describes and analyzes the social behavior of Punk community members in the city of Blitar in daily living habits and the factors behind some young people in the city of Blitar join the Punk community. Methods of data collection using observation, in-depth interviews and documentation. Data analysis techniques using the model Strauss and Corbin (Grounded Theory). Result of research: First, social behavior of Punk community members in Blitar city consists of: (1) appropriate behavior (adeuat) with the norms in society, such as commemorating Earth Day, International Labor Day, distributing ta'jil in Ramadhan, and conduct humanitarianfund raising. (2) deviant social behaviors such as hanging out after maghrib, mentatto and piercing certain body parts, alcoholic beverages of Javanese wine type, wearing black clothes, putting emblems on clothes, conflicts between friends, sleeping and bathing in makeshift place, wearing botts shoes, chain accessories and pendant pig pendants. Second, the factors behind some young people in the city of Blitar join the Punk community consisting of: (1) internal factors: (a) desire to channel their talents in music, (b) actualize themselves in society, (c) and comfortable outdoors, (d) feeling sympathetic after seeing the lives and activities of members of the Punk community. (2) External factors such as: (a) lack of attention and affection from parents, (b) lack of religious education in the family environment, (c) interested in family members who have joined earlier in community Punk, (d) fellow friends around the house, (e) association with fellow friends in the school environment.